Bare die connections via aerosol jet technology for millimeter wave applications. Issue 5 (21st February 2019) - Röhrl, Franz Xaver; Jakob, Johannes; Bogner, Werner; Weigel, Robert; Zorn, Stefan
Abstract: This paper presents a comparison of chip connections using aerosol jet (AJ) and bond technology on low-cost printed circuit board (PCB) substrates. First, the behavior of the used gap filler material and the used silver ink for AJ technology on PCBs are characterized. In addition to comparing the radio frequency (RF) performance (DC to 67 GHz) of the two technologies, the mechanical stability is also compared. While the AJ technology transitions score above all for their RF performance and the lower requirements (surface finish, pad size, and adhesion) on the PCB, the bonding technology has clear advantages, especially with a different coefficient of thermal expansion values of the substrates to be connected. Finally, the measurement results of a complete package are shown, whereby the chip connection is realized once by means of AJ and once by bonding wires.